2019
DOI: 10.1021/acs.inorgchem.9b01660
|View full text |Cite
|
Sign up to set email alerts
|

Homo- and Heterosolvent Modifications of Hofmann-Type Flexible Two-Dimensional Layers for Colossal Interlayer Thermal Expansions

Abstract: Two-dimensional Hofmann-type coordination polymers of type Mn­(H2O)2[Pd­(CN)4]·xH2O (1· x H 2 O; x = 0, 1, and 4), Mn­(H2O)­(MeOH)­[Pd­(CN)4]·2MeOH (2·2MeOH), and Mn­(MeOH)2[Pd­(CN)4]·MeOH (3·MeOH) have been synthesized. The homosolvent-bound 1·4H 2 O, 1·H 2 O, and 3·MeOH polymers consist of undulating layer structures, whereas the structure of heterosolvent-bound 2·2MeOH consists of “Janus-like” flat layers in which water-bound and MeOH-bound-sides are present. 1·4H 2 O and 1·H 2 O exhibited aniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 61 publications
1
12
0
Order By: Relevance
“…We used scanning transmission electron microscopy (STEM) [9] to comprehend the overall crystal structure of the fully-dehydrated FePd-(CN) 4 CP.I na ni nterpenetrated 3D PtS-type FePd(CN) 4 network, the coordination geometry of Fe II is not only anomalously distorted but can also act as af lexible node, inducing anisotropic thermal expansion (TE) behaviors, including uniaxial positive TE and large NTE along the other axes. 2 •4 H 2 Odemonstrated that its structure is similar to that of previously reported compounds with ac yanide-bridged 2D layer, [10] with two water molecules coordinated to the axial sites of the Fe II ions and the other four in the lattice (Figure 1a;S upporting Information, Table S1). Theb ond lengths of FeÀNa nd FeÀOa re 2.142(3) and 2.164(3) ,r espectively.T he infrared (IR) spectrum of 1(H 2 O) 2 •4 H 2 Odisplays the characteristic stretching mode of the bridging CN À ligands at 2169 cm À1 ,along with peaks corresponding to water molecules (Supporting Information, Figure S1).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We used scanning transmission electron microscopy (STEM) [9] to comprehend the overall crystal structure of the fully-dehydrated FePd-(CN) 4 CP.I na ni nterpenetrated 3D PtS-type FePd(CN) 4 network, the coordination geometry of Fe II is not only anomalously distorted but can also act as af lexible node, inducing anisotropic thermal expansion (TE) behaviors, including uniaxial positive TE and large NTE along the other axes. 2 •4 H 2 Odemonstrated that its structure is similar to that of previously reported compounds with ac yanide-bridged 2D layer, [10] with two water molecules coordinated to the axial sites of the Fe II ions and the other four in the lattice (Figure 1a;S upporting Information, Table S1). Theb ond lengths of FeÀNa nd FeÀOa re 2.142(3) and 2.164(3) ,r espectively.T he infrared (IR) spectrum of 1(H 2 O) 2 •4 H 2 Odisplays the characteristic stretching mode of the bridging CN À ligands at 2169 cm À1 ,along with peaks corresponding to water molecules (Supporting Information, Figure S1).…”
Section: Introductionsupporting
confidence: 82%
“…Thermogravimetry-differential thermal analysis (TG-DTA) showed that the weight loss occurred in two steps:through the removal of four lattice water molecules at 340 Kand two bound water molecules at 390 K(Supporting Information, Figure S2), while no weight loss was observed for the fully-dehydrated form, up to 600 K. ( Figure 1b,c). [10] Compound 1 was obtained by the thermal treatment of 1(H 2 O) 2 •4 H 2 Oa t5 53 Kf or 30 min (Supporting Information, Figure S3). TheI Rs pectrum of 1 shows the characteristic stretching mode of CN À ligands at 2181 cm À1 (Supporting Information, Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“… Crystal structures of a) 1 (H 2 O) 2 ⋅4 H 2 O and b) Mn(H 2 O) 2 Pd(CN) 4 ⋅H 2 O for comparison . c) PXRD results for 1 (H 2 O) 2 ⋅4 H 2 O, 1 (H 2 O) 2 ⋅H 2 O, and 1 .…”
Section: Resultsmentioning
confidence: 99%
“…But NTE behaviour has been investigated much less extensively for Hofmann-like 2D compounds with organic ligands. 9,[11][12][13][14] Research on cyano-bridged CPs without any other organic ligands indicated the mechanism of the fence effect to be due to the transverse CN vibrational modes. 32 Consequently, in that previous work, a large compound displaying anisotropic TE shows highly bent, zig-zag cyano-bridged layer structures.…”
Section: Thermal Expansion Behaviorsmentioning
confidence: 99%
“…Recently, negative thermal expansion (NTE) behavior in Hofmann-like 2D layer has been investigated. 9,10 However, there are few reports of a coexistence of SCO with anisotropic TE. An ability to consider a combination of lattice expansion (NTE) and rapid lattice contraction (SCO), i.e.…”
Section: Introductionmentioning
confidence: 99%